Optimising water requirement for nursery rearing of rohu Labeo rohita (Hamilton, 1822) in large outdoor concrete tanks: influence of water depth on seed performance - Das, Pratap Chandra; Kamble, Suhas Prakash (Indian Journal of Fisheries, 2019)
A study was conducted to find the optimum water depth requirement for nursery rearing of rohu Labeo rohita (Hamilton, 1822). Nine concrete tanks of 50 m2 each (10 x 5 x 1.2 m) were grouped into three treatments T1, T2 and T3 and were filled upto 1.0, 0.75 and 0.5 m water depths, respectively. Each tank was stocked with 0.5 lakh hatchery produced spawn and reared for 20 days. The study revealed significant influence of water depth on growth and survival of fry (p<0.05). Though the final length of fry did not differ among the treatments (p>0.05), T3 with 0.5 m water depth showed significantly lower survival, final body weight and specific growth rate than the other two treatments (p<0.05), whereas tanks with 1.0 and 0.75 m water depths showed almost similar survival, final weight and SGR (p>0.05). Assessment of water use for production of every 1000 fry revealed significant reduction in total water use (TWU) with decreased water depth (p<0.05), while the consumptive water use (CWU) in terms of water exchange and replenishment did not differ between water depth treatments of 1.0 and 0.75 m. The results of the study indicate 0.75 m to be the ideal water depth with better water use efficiency for fry production of the species.